Disposition and bioavailability of inulin and free sugar in untreated and dilute acid pretreated Agave tequilana leaves. (November 2017) - Close, Dan; Rodriguez, Miguel; Hu, Rongbin; Yang, Xiaohan
Abstract: Industrially, the Agave tequilana plant is most commonly associated with beverage production, which requires it to be grown for 8–10 year before harvesting. However, its robust growth characteristics and low water usage requirements suggest that it could also be utilized as a substrate for alternative fermentation processes that do not require such long crop turnover times. Therefore, a study was undertaken to characterize the feasibility of utilizing the leaves from two year-old plants as a microbial fermentation biomass substrate. Quantitative saccharification revealed the carbohydrate concentration of two year-old A. tequilana leaves to be 633 mg g −1 dry weight biomass. HPLC analysis identified the primary carbohydrates as glucans, with minor contributions from xylans, galactans, arabinanas, and mannans. Fructose was observed predominantly as inulin. The direct use of unpretreated A. tequilana leaf biomass as a sole carbon source could support yeast growth, however, dilute acid pretreatment removed sufficient levels of carbohydrates to prevent the growth of wild type or inulinase-expressing yeast strains. Up to 133.5 g kg −1 of soluble carbohydrates and 69.6 g kg −1 of soluble inulin were extracted in the pretreatment soakate and 4.0 g kg −1 of soluble carbohydrates and 1.3 g kg −1 of soluble inulin remained in the biomass post processing. Inulinase gene expression did not significantly improve yeast growth rates, but permitted up to 6.3 g kg −1 of the available soluble inulin from the dilute acid pretreatment soakate to be metabolized towards cellular growth. Highlights: Two-year old Agave tequilana leaves contain sufficient soluble sugar to support yeast fermentation without pretreatment. Dilute acid pretreatment of two-year-old Agave tequilana leaves efficiently solubilizes both inulin and free carbohydrates. Up to 69.3 g kg −1 inulin is unaffected by dilute acid pretreatment of Agave tequilana leaves and remains polymerized. Dilute acid pretreatment wash waste can be re-introduced into the fermentation to capture additional carbohydrates.